Di- and Tetrairon(III) μ-Oxido Complexes of an N3S-Donor Ligand: Catalyst Precursors for Alkene Oxidations - Das, Biswanath; Al-Hunaiti, Afnan; Sánchez-Eguía, Brenda N.; Zeglio, Erica; Demeshko, Serhiy; Dechert, Sebastian; Braunger, Steffen; Haukka, Matti; Repo, Timo; Castillo, Ivan; Nordlander, Ebbe (Frontiers in Chemistry, 2019)
The new di- and tetranuclear Fe(III) μ-oxido complexes [Fe4(-O)4(PTEBIA)4](CF3SO3)4(CH3CN)2] (1a), [Fe2(-O)Cl2(PTEBIA)2](CF3SO3)2 (1b), and [Fe2(-O)(HCOO)2(PTEBIA)2] (ClO4)2(MeOH) (2) were prepared from the sulfur-containing ligand (2-((2,4-dimethylphenyl)thio)-N,N-bis((1-methyl-benzimidazol-2-yl)methyl)ethanamine (PTEBIA). The tetrairon complex 1a features four -oxido bridges, while in dinuclear 1b, the sulfur moiety of the ligand occupies one of the six coordination sites of each Fe(III) ion with a long Fe-S distance of 2.814(6) Å). In 2, two Fe(III) centers are bridged by one oxido and two formate units, the latter likely formed by methanol oxidation. Complexes 1a and 1b show broad sulfur-to-iron charge transfer bands around 400-430 nm at room temperature, consistent with mononuclear structures featuring Fe-S interactions. In contrast, acetonitrile solutions of 2 display a sulfur-to-iron charge transfer band only at low temperature (228 K) upon addition of H2O2/CH3COOH, with an absorption maximum at 410 nm. Homogeneous oxidative catalytic activity was observed for 1a and 1b using H2O2 as oxidant, but with low product selectivity. High valent iron-oxo intermediates could not be detected by UV-vis spectroscopy or ESI mass spectrometry. Rather, evidence suggest preferential ligand oxidation, in line with the relatively low selectivity and catalytic activity observed in the reactions.